Scripture and cosmology : reading the Bible between the ancient world and modern science - Greenwood, Kyle (Downers Grove, IL : InterVarsity Press, 2015)
"As Kyle Greenwood shows, the cosmic language of the Bible is also that of the ancient Near Eastern palace, temple, and hearth. Greenwood also helps us see how the best Christian thinkers have viewed the cosmos in light of Scripture and have grappled with new understandings, as science has advanced from Aristotle to Copernicus to Galileo and the galaxies of deep space. It's a compelling story that both illuminates the text of Scripture and helps us find our own place in the tradition of faithful Christian thinking and interpretation." -- Back Cover
Scripture in context -- Scripture and cosmos in cultural context -- Ancient Near Eastern cosmologies -- Cosmology in scripture -- Cosmology and cosmogony in scripture -- Cosmology and scripture in historical context -- Scripture and Aristotelian cosmology -- Scripture and Copernican cosmology -- Scripture and science -- Cosmology and the authority of scripture -- The authority of scripture and the issue of science.
Includes bibliographical references and indexes.
Keywords: Biblical cosmology; Bible and science